Peningkatan Pemanfaatan Pekarangan Rumah Untuk Menunjang Kesejahteraan dan Pendidikan Keluarga - Bonaventura R. Seto Se; Murdaningsih Murdaningsih (Jurnal Impresi Indonesia, 2025)
This study explores the role of education in enhancing home garden utilization for family nutrition in Watumite Village. It employs methods such as field observations, interviews, socialization, technical training, and periodic evaluations. Field observations assessed the condition and potential of home gardens, while interviews helped identify residents' knowledge and practices. Socialization efforts highlighted the importance of home gardens for improving nutrition, supported by educational materials like pamphlets and guidebooks on gardening techniques. Technical training involved practical sessions on cultivating vegetables and medicinal plants, with direct demonstrations on planting and care. The program included ongoing assistance to help residents implement the techniques learned, alongside regular monitoring and evaluation to gauge success and offer feedback. The final evaluation assessed the impact of education on home garden utilization and family nutrition. Results indicated that education significantly increased residents' gardening knowledge and skills. Periodic support was crucial for program sustainability, leading to a marked rise in home garden use for growing vegetables and medicinal plants, positively affecting family nutrition. The study concludes that structured and sustainable education is an effective strategy for improving nutrition through home gardens in rural communities.